Development of a computer assisted learning (CAL) for electric and electronic studies (EEES) : electromagnetism - 255544 Loh, Kiong Soon (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Teknologi serta Pendidikan (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2008